FUNDAMENTALS OF WATER USE IN THE CATCHMENT AREAS OF THE ILI RIVER BASIN - Mustafayev Zhumakhan Suleimenovich,; Ryskulbekova Laura Meldakhanovna, (Academic Journal of Physical and Chemical Sciences, 2020)
Based on the long-term information and analytical materials «Balkhash-Alakol Basin Inspectorate for Regulation of Use and Protection of Water Resources» of the Committee for Water Resources of the Ministry of Agriculture of the Republic of Kazakhstan, the environmental indicator of specific water availability, which availability high water availability, ensuring sustainable development of economic sectors, but not ensuring the natural and environmental sustainability and safety of functioning of Lake Balkhash, as a geographic water body. The location in the arid and semi-arid zones, as well as the features of the formation of hydrological flow in the catchment areas of the Ili River basin, which determines the environment-forming system with socio-economic conditions and natural and technogenic objects that determine the level of water supply for water management sites, require the need for coordination of water management in order to prevent possible negative changes in watercourses and reservoirs that perform important environmental functions in the Ili-Balkhash basin, that is, to ensure natural and environmental sustainability and safe functioning of Lake Balkhash as a geographic water body.